Stress and Fatigue in Operators Under Radiofrequency Electromagnetic Radiation and Shift Work - Vangelova K. (Sciendo, 2014)
The aim was to study the effect of radiofrequency electromagnetic radiation (EMR) on stress indices, health complaints and fatigue of operators working fast-rotating extended shifts. Working conditions, job content, job control, social support, health complaints and fatigue were followed in 220 operators, 110 exposed to EMR and 110 control operators, matched by age and sex. The EMR was measured and time-weighted average (TWA) was calculated. The excretion rates of stress hormones cortisol, adrenaline and noradrenaline were followed during the extended shifts in 36 operators, working at different levels of exposure and 24-hour exposure was calculated. The exposed group pointed more problems with the working conditions, including EMR, noise, currents and risk of accidents, more health complaints and higher level of fatigue. The most common health complaints were mental and physical exhaustion after work, pains in the chest, musculoskeletal complaints, headache, and apathy. High level EMR exposure (TWAmean = 3.10 μW/cm2, TWAmax = 137.00 μW/cm2) significantly increased the 24-hour excretion of cortisol and noradrenaline, whereas the increase of adrenaline excretion did not reach significance, as well as hormone excretion rates under low level exposure (TWAmean = 1.89 μW/cm2, TWAmax = 5.24 μW/cm2). In conclusion, higher number of health complaints, higher stress hormone excretion rates and fatigue were found in operators under EMR.